Conception of the Present-day Pension System as a Result of Transformation Processes in Global Determination - Rad, N.S. (Економічний вісник Донбасу, 2015)
The article deals with some urgent problems related to the development of pension system in Ukraine in the context of global transformation processes. Identified and specified are conditions for it to be improved. It is emphasized that endowment retirement insurance is capable efficiently confront present-day risks and challenges, especially rapid ageing of population. The main forming factors of retirement insurance systems of different countries are analyzed. Based on their analysis it is assumed that problems related to economic and financial sectors grow into global imbalances. The basic features of risk-resistant model of the national pension system are specified. It is observed that the key element of the efficient concept of the national pension system is synthesis of social and economic components in the context of adhering to the principles of social welfare state. The research is based on a system approach using general scientific methods: generalization, pooling, analysis and synthesis. We used abstract-logical method for making conclusions. The lines for improvement of the concept of pension system in the context of the peculiarities of the national cultural and historic development and contemporary trends, risks and challenges of social development are proposed. В статті досліджено окремі аспекти розвитку національної пенсійної системи в контексті світових трансформаційних процесів. Виявлено та окреслено умови її модернізації. Підкреслено, що змішані системи пенсійного страхування здатні найбільш ефективно протистояти сучасним ризикам та викликам, зокрема стрімкому старінню населення. Проаналізовано основні формоутворюючі показники систем пенсійного страхування різних країн. На підставі їх аналізу відмічено, що проблеми економічної і фінансової сфери набули характеру глобальних дисбалансів. Визначені основні риси ризикосталої моделі вітчизняної пенсійної системи. Відмічено, що ключовим звеном ефективної концепції національної пенсійної системи є синтез соціальної та економічної складових в контексті спрямування до принципів соціальної держави. В ході дослідження була застосована сукупність загальнонаукових методів: узагальнення, групування, аналізу досліджуваних категорій. Теоретичні узагальнення та висновки будувались на підставі абстрактно-логічного методу. Запропоновано напрямки удосконалення концепції пенсійної системи в контексті особливостей національного культурно-історичного розвитку та сучасних тенденцій, ризиків та викликів суспільного розвитку. В статье исследованы отдельные аспекты развития национальной пенсионной системы в контексте мировых трансформационных процессов. Выявлены и обозначены условия ее модернизации. Подчеркнуто, что смешанные системы пенсионного страхования способны наиболее эффективно противостоять современным рискам и вызовам, в частности стремительному старению населения. Проанализированы основные формообразующие показатели систем пенсионного страхования различных стран. На основании их анализа отмечено, что проблемы экономической и финансовой сферы приобрели характер глобальных дисбалансов. Определены основные черты рискоустойчивой модели отечественной пенсионной системы. Отмечено, что ключевым звеном эффективной концепции национальной пенсионной системы является синтез социальной и экономической составляющих в контексте следования принципам социального государства. В ходе исследования была применена совокупность общенаучных методов: обобщения, группировки, анализа исследуемых категорий. Теоретические обобщения и выводы строились на основании абстрактно-логического метода. Предложены направления совершенствования концепции пенсионной системы в контексте особенностей национального культурно-исторического развития и современных тенденций, рисков и вызовов общественного развития.